IMPLEMENTASI INOVASI DESA GISA (GERAKAN INDONESIA SADAR ADMINISTRASI KEPENDUDUKAN) DALAM PELAYANAN KARTU IDENTITAS ANAK (KIA) DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN SEMARANG - Saraswati,, Indarti; Lituhayu, Dyah; Larasati Setianingsih, Endang (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2024)
This study focuses on the implementation of the Desa GISA innovation launched by the Department of Population and Civil Registration (Dispendukcapil) of Semarang Regency to bring administrative services closer to the community and make them more accessible, including the issuance of Child Identity Cards (KIA). Although this innovation was designed to increase KIA ownership, data shows that KIA ownership in Semarang Regency actually decreased in 2022, placing it as the eighth lowest in Central Java Province. This study aims to analyze the implementation of the Desa GISA innovation in KIA services and to identify the supporting and inhibiting factors. The study uses Van Meter and Horn's policy implementation theory and a qualitative descriptive approach, with primary data from interviews and secondary data from other sources. The findings reveal that governance and infrastructure are not yet optimal due to mismatches in document processing times and inadequate facilities. However, the competence of human resources, working relationships, and innovation development have achieved optimal results. The inhibiting factors in the implementation of the Desa GISA innovation include a lack of resources and low public awareness in managing population documents. Supporting factors include the implementers' understanding of standards, political support, effective inter-organizational communication, and the absence of fees for document processing. It is recommended that Dispendukcapil enhance socialization through social media and provide training for officials to optimize the implementation of this innovation.